1987
DOI: 10.1210/endo-120-1-381
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Administration of Corticotropin-Releasing Factor Increases Pituitary Corticotroph Number*

Abstract: The effect of chronic administration of CRF on rat pituitary morphology was studied. Experimental animals received CRF (10 micrograms/day) over a period of 52 days by means of sc osmotic pumps changed at 10- to 14-day intervals. The average 0800 h plasma corticosterone levels in the treated animals were significantly greater than control values [7.52 +/- 0.99 (+/- SE) vs. 1.14 +/- 0.5 micrograms/dl; P less than 0.001]. The CRF-treated animals also had a significantly greater adrenal weight (16.44 +/- 1.38 vs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0
1

Year Published

1988
1988
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 159 publications
(54 citation statements)
references
References 36 publications
5
47
0
1
Order By: Relevance
“…Dramatically increased intensity of ACTH-immunoreactive pituitary cells occurs through the end of the second trimester. In the rat, increased corticotroph proliferation occurs in response to CRH (37), and the mature adult pituitary cell population consists of 10-20% corticotrophs (35 (39,40). Using a 600-bp radiolabeled human cRNA excluding the first exon, the 400-bp protected human pituitary LIF mRNA detected in fetal pituitary tissue is consistent with divergent splicing of the human LIF gene, as has been suggested for the murine LIF gene (41).…”
Section: Methodssupporting
confidence: 67%
“…Dramatically increased intensity of ACTH-immunoreactive pituitary cells occurs through the end of the second trimester. In the rat, increased corticotroph proliferation occurs in response to CRH (37), and the mature adult pituitary cell population consists of 10-20% corticotrophs (35 (39,40). Using a 600-bp radiolabeled human cRNA excluding the first exon, the 400-bp protected human pituitary LIF mRNA detected in fetal pituitary tissue is consistent with divergent splicing of the human LIF gene, as has been suggested for the murine LIF gene (41).…”
Section: Methodssupporting
confidence: 67%
“…Animal and clinical studies have demonstrated that HPA axis activation by corticotropinreleasing hormone (CRH) or by stress leads to an increase in the number and size of corticotropes in the pituitary gland (Asa et al, 1992;Carey et al, 1984;Gertz et al, 1987;Westlund et al, 1985). This increase in the size and numbers of corticotropes can increase pituitary volume in humans as Figure 3 Individual measures of pituitary volumes in first-episode patients (n ¼ 77; one subject on which we had no medication history was excluded from this analysis) divided by antipsychotic treatment (free, n ¼ 18; atypicals, n ¼ 26; typicals, n ¼ 33).…”
Section: Discussionmentioning
confidence: 99%
“…Constant infusion of CRH was performed as described (33). Groups of n ϭ 5-6 adult CRH KO female mice maintained on a 12:12 LD cycle (lights on at 0700, lights out at 1900) underwent subcutaneous osmotic minipump placement (ALZA Corp., Palo Alto, CA) and received infusion of either vehicle alone (1% acetic acid, 1 mg/ml ascorbate, and 10 mg/ml BSA) or daily doses of 0.1, 0.25, 0.5, or 1 g/d of CRH in vehicle.…”
Section: Methodsmentioning
confidence: 99%